2017
DOI: 10.12659/msm.908004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Insulin-Like Growth Factor 1 Are Associated with Osteosarcoma Risk and Prognosis

Abstract: BackgroundInsulin-like growth factor 1 (IGF-1) gene plays an important role in bone and soft tumors. IGF-1 gene polymorphisms have been revealed to be correlated with the carcinogenesis and progression of solid malignancies. We therefore hypothesized that IGF-1 genetic polymorphisms might be associated with the risks and outcomes of osteosarcomas in Chinese individuals.Material/MethodsThis study included 173 conventional osteosarcoma individuals and 175 tumor-free controls. Five single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…For example, at 48 hours of exposure to 50 μg/ml of GO, the total percentage of apoptotic cells for the U2OS IGF-1 knocked out, and U2OS IGFBP3 knocked out were 49.1% and 45.9%, respectively compared to 26.28% for U2OS. Knocking out IGF-1 was slightly more effective than knocking out the IGFBP3 gene [51,52]. The results from flow cytometry and morphological changes support the hypothesis that GO has a toxic effect on human cancer cells but not on healthy cells.…”
Section: Igf Plays a Vital Role In The Growth And Development Of Tisssupporting
confidence: 66%
See 1 more Smart Citation
“…For example, at 48 hours of exposure to 50 μg/ml of GO, the total percentage of apoptotic cells for the U2OS IGF-1 knocked out, and U2OS IGFBP3 knocked out were 49.1% and 45.9%, respectively compared to 26.28% for U2OS. Knocking out IGF-1 was slightly more effective than knocking out the IGFBP3 gene [51,52]. The results from flow cytometry and morphological changes support the hypothesis that GO has a toxic effect on human cancer cells but not on healthy cells.…”
Section: Igf Plays a Vital Role In The Growth And Development Of Tisssupporting
confidence: 66%
“…There is evidence that IGF-1 related pathways are involved in osteosarcoma progression. There is downstream of signaling pathways such as the MAPK, PI3K-Akt, and NF-kB pathways [51,52].…”
Section: Igf Plays a Vital Role In The Growth And Development Of Tissmentioning
confidence: 99%
“…However, the relatively small sample size of the three studies in this meta-analysis may reduce the statistical strength of the test correlation, leading to debates on the results and impact on the conclusions (11,19,21). Compared with different races and populations, our meta-analysis showed that there was no significant correlation between IGF1rs5742612 polymorphism and malignant tumor susceptibility in Iran (16,19) or South Korea (20) population, which is inconsistent with the Chinese population (17,18,21). Due to the diversity and potential differences in malignant tumor susceptibility in the population, the results of the current meta-analysis may not be generalized, so further research is needed on other races and populations to provide additional evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms, including rs6214, rs6220, rs5742714, rs1549593, 2,373,722, 10,735,380, 12,821,878, rs2195239, rs2162679, rs35767, rs5742612, and rs7965399, have been reported to be related to disease occurrence [15, 18, 2023, 3234]. Some of these important polymorphisms, such as rs6214, rs6220, and rs5742714,are located in the 3’UTR region of IGF1 , while others, such as rs1549593, 2,373,722, 10,735,380, 12,821,878, rs2195239, and rs2162679, are located in the intron of IGF1 .…”
Section: Discussionmentioning
confidence: 99%